Method Development and Validation of Anti-depressant Bupropion by RP-HPLC - Batool, Naghma; Bansal, Mukesh; Agrawal, Dilip (Journal of Biomedical and Pharmaceutical Research, 2022)
Bupropion is an atypical antidepressant and smoking cessation aid. The drug is a non-tricyclic antidepressant and differs from most commonly prescribed antidepressants such as SSRIs, as its primary pharmacological action is thought to benorepinephrine-dopamine reuptake inhibition. A new sensitive and rapid HPLC method was developed for the determination of buproprion in bulk and pharmaceutical dosage forms; it was validated according to ICH and FDA guidelines. The HPLC analysis was performed on the Alliance Waters e2695 Separations Module system equipped with a Waters X – Bridge C-18 5µm, 4.6 X 150 mm column 5, with a mixture of Acetonitrile: Ammonium bicarbonate (5mM) pH-9 adjusted with 1% Ammonium hydroxide (50:50, %v/v). Flow rate was 1 ml/min quantification was done by PDA detector at 254nm. The proposed method showed linearity in the concentration range of 50 to 250 ppm for Bupropion. The linear regression equation of Bupropion was found to be y = 6E+06x + 91344 and correlation coefficient value was found to be 0.997 indicating a high degree of linearity for the drug. The proposed method was stable except the basic condition during analysis. The stability of the analyte solution was determined at interval of 1st, 2nd, 3nd, 4th and 5th day. The low values of %recovery and %C.V. showed that the method is precise within the acceptance limit of 5% (according to ICH guidelines).The limit of detection (LOD) of Bupropion was 0.5 ppm and limit of quantification (LOQ) was 2.0 ppm respectively. The proposed method showed excellent linearity, accuracy, precision, specificity, robustness, LOD, LOQ, and system suitability results within the acceptance criteria.